2003
DOI: 10.1159/000072468
|View full text |Cite
|
Sign up to set email alerts
|

Mutism after Posterior Fossa Tumour Resection in Children: Incomplete Recovery on Long-Term Follow-Up

Abstract: Introduction: Mutism after posterior fossa tumour resection is generally said to be transient. Our experience suggested that speech did not usually normalise, and that mutism was associated with neurologic deficits that did not recover fully. Methods: Children with mutism after posterior fossa tumour resection, and alive more than 2 years post-operatively, were reviewed retrospectively. Charts were reviewed and parents contacted to ascertain details about mutism, associated neurologic deficits, and the most re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(49 citation statements)
references
References 11 publications
1
48
0
Order By: Relevance
“…Replacement of the bone flap protects the area of surgical dissection and improves postoperative healing in addition to preserving the anatomy for potential future resections [18]. During the procedure, traction on the cerebellar hemispheres should be minimized to diminish development of pseudobulbar symptoms and cerebellar mutism [38,39,40]. …”
Section: Treatmentmentioning
confidence: 99%
“…Replacement of the bone flap protects the area of surgical dissection and improves postoperative healing in addition to preserving the anatomy for potential future resections [18]. During the procedure, traction on the cerebellar hemispheres should be minimized to diminish development of pseudobulbar symptoms and cerebellar mutism [38,39,40]. …”
Section: Treatmentmentioning
confidence: 99%
“…The 5-year survival rate in their study was slightly better but not significant for those with total tumor removal than for those with subtotal tumor removal (56 vs. 47%). None of our patients was diagnosed as having cerebellar mutism, which was reported to occur in 3.7-8.5% of children after resection of posterior fossa tumor [13,14]. The low incidence in our study is questionable because of its small sample size.…”
Section: Discussionmentioning
confidence: 55%
“…Huber et al 46 considered that motor speech deficits persist for a long period of time (> 5 years), and similar findings were made by other authors. 52,81,92 Lastly, Robertson et al 82 tried to analyze the neurological outcome of their patients, and they found that there is a significant relationship among the level of initial severity of the syndrome and the severity of ataxia and language dysfunction and global intellectual handicap after 1 year. It is worth mentioning than in a developing child such persistent symptoms have a lasting impact on global language and cognitive skills.…”
Section: Outcomementioning
confidence: 99%